2018
DOI: 10.1242/jcs.219386
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule dynamics regulation reconstituted in budding yeast lysates

Abstract: Microtubules (MTs) are important for cellular structure, transport of cargoes and segregation of chromosomes and organelles during mitosis. The stochastic growth and shrinkage of MTs, known as dynamic instability, is necessary for these functions. Previous studies to determine how individual MT-associated proteins (MAPs) affect MT dynamics have been performed either through studies, which provide limited opportunity for observation of individual MTs or manipulation of conditions, or studies, which focus either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 75 publications
(86 reference statements)
2
60
0
Order By: Relevance
“…Extracts from S. cerevisiae provide many the advantages of extract-based experimentation, but with the added benefit of leveraging the power of yeast genetics. Budding yeast extracts have been useful for studying microtubule and actin polymerization (Bergman et al, 2018; Michelot and Drubin, 2014). In this study, we employed a similar extract protocol to investigate the biophysical properties governing septin filament polymerization in budding yeast, where septins were first discovered and their biology is arguably best understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts from S. cerevisiae provide many the advantages of extract-based experimentation, but with the added benefit of leveraging the power of yeast genetics. Budding yeast extracts have been useful for studying microtubule and actin polymerization (Bergman et al, 2018; Michelot and Drubin, 2014). In this study, we employed a similar extract protocol to investigate the biophysical properties governing septin filament polymerization in budding yeast, where septins were first discovered and their biology is arguably best understood.…”
Section: Discussionmentioning
confidence: 99%
“…To determine how septin-regulatory proteins influence reactions, we analyzed septin filaments in whole cell extracts prepared from either wild-type or mutant S. cerevisiae cells on SLBs. Extracts were prepared by adapting previously published protocols from studies investigating F-actin and microtubule assembly (Bergman et al, 2018;Michelot and Drubin, 2014). Asynchronous cultures of wild-type haploid cells expressing GFP-Cdc3 from the endogenous locus were harvested during log-phase growth for Alternatively, unknown factors (including regulators) may promote filament extension (perhaps by expanding the angles of contact between octamers sufficient for annealing) or stabilize filaments from fragmentation.…”
Section: Septins From Cell Extracts Have a Higher Apparent Annealing Affinity And Polymerize Into Ringsmentioning
confidence: 99%
“…As previously reported, the Kip3ΔT-LZ mutant protein did not accumulate on the plus ends of microtubules and it was unable to destabilize their plus ends and cause depolymerization (Su et al, 2011) (Figure S2b). Similarly, in a kip3 Δ lysate, there was also altered microtubule dynamics, specifically a diminished catastrophe frequency (Bergman et al, 2018) (Figure S2b). Because of the reduced microtubule catastrophe frequency, we observed that in kip3 Δ T-LZ lysates the kinetochore rarely reached the plus ends of polymerizing microtubules, despite it’s faster velocity.…”
Section: Resultsmentioning
confidence: 93%
“…We thus employed an alternate strategy to assemble microtubules from either wild-type or mutant tubulin (Bergman et al, 2018). Specifically, we prepared concentrated cell lysates from either wild-type or tub1 G437R cells (both of which possessed wild-type TUB3), and incubated them in microscope chambers in which pre-assembled microtubule seeds were affixed.…”
Section: G437r Tubulin and Microtubules Exhibit Reduced Interaction With The Dynein Regulator She1mentioning
confidence: 99%
“…Microtubules were polymerized from pre-assembled coverslip-immobilized microtubule seeds and concentrated cell extracts as previously described (Bergman et al, 2018), but with minor modifications. Overnight cultures of cells (3 ml in YPAD media) with respective -tubulin content (e.g., wild-type, tub1 G437R , etc) were diluted into 200 mL of YPAD, and grown for 16 hours before being transferred to 800 mL YPAD.…”
Section: Microtubule Reconstitutions Using Cell Lysatesmentioning
confidence: 99%